The Impact of Regional Trade Agreements and Trade Facilitation in the Middle East North Africa Region - Dennis, Allen (World Bank, Washington, DC, 2012)
The Middle East and North Africa (MENA) region's trade performance over the past two decades has been disappointing. Efforts to boost trade through a plethora of regional trade agreements (RTAs) are underway. This study examines the potential contribution of regional trade agreements, as well as trade facilitation improvements, in enhancing the development prospects of the region. Using the Global Trade Analysis Project (GTAP) model and database, both intra-regional integration and integration with the European Union are observed to have a favorable impact on welfare in the MENA region. The welfare gains from integrating with the European Union are observed to be at least twice as much as intra-regional integration. Furthermore, these welfare gains are observed to at least triple when the implementation of the RTAs is complemented with trade facilitation improvements.